Hubungan antara Yoga dengan Siklus Menstruasi - Indah Purnama Sari; . Kiyatno; Diffah Hanim (Nexus Biomedika, 2014)
Background: Disturbed menstrual cycle often causes anxiety women. Menstruation disturbance can affect daily activities, that can decrease productivity. Nutrition and physical activities can affect regularity of menstrual cycle. Yoga is a popular physical activity recently that can influence hormone reproduction. This study aims to investigate the relationship between Yoga and menstrual cycle. Method: This research was an observational analytic research with cross sectional approach. There were 63 subjects of research that were chosen using purposive sampling of women who took Yoga course in Ganep's Surakarta. Independent variable of this research was Yoga. While dependent variable of this research was menstrual cycle. Data collected by direct interview with a list of questions to respondent were analyzed using bivariate Chi-Square, Contingency coefficient, and Odds. Result: The result of Chi-Square test showed there was significant correlation between Yoga and menstrual cycle (p = 0.000). Coefficient of contingency test showed that 43.5% women who took Yoga course had regular menstrual cycle (C = 0.43; and p =0.000). While Odds Ratio test showed that women who took Yoga course had possibility 9.86 times to have regular menstrual cycle (OR = 9.86; CI 95% 2.87 - 34.95; and p = 0.000). Result of Research: There is significant correlation between Yoga and menstrual cycle. Keywords: Yoga, menstrual cycle